Wettability-dependent Wave Velocities and Attenuation in Granular Porous Media - Li, J.X.; Rezaee, Reza; Müller, T.M.; Madadi, M.; Ma, R.; Sarmadivaleh, Mohammad (SOC EXPLORATION GEOPHYSICISTS, 2022)
Understanding seismic wave propagation in granular porous media is important for subsurface characterization. The presence of fluids, their distribution and the prevailing wettability condition results in additional complexities. While it is known that wave propagation in dry granular porous media is dominated by the presence of force chains, their influence in (partially) saturated granular porous media with different wettability conditions remains largely unexplored. To make progress in this direction, we design laboratory experiments by combining core flooding and ultrasonic measurements in glassbead packings that are chemically treated to alternate the wettability. The P- and S-wave velocity-saturation relation and attenuation-saturation relation are retrieved from the waveforms for both water- and gas-wetting samples. The results show that there is a transition from an attenuating but stable P-wave pulse at low and moderate saturation to a set of incoherently scattered waves at high saturation. The incoherent scattering in the gas-wetting case is negligibly small, whereas it is more pronounced in the water-wetting case. We interpret these observations in terms of the wettability-dependent ability for water to penetrate into grain contacts. In the water-wetting case, liquid bridges are thought to locally reinforce the force chains and to increase their characteristic length scale. This leads to an increase in P-wave velocity and promotes incoherent scattering since the ratio of dominant wavelength to characteristic length scale decreases. In the gas wetting case, however, the presence of gas prevents the water from direct contact with the glass beads and therefore stops the formation and growth of the liquid bridges within the force chain network.